Tarsal tunnel syndrome caused by an uncommon ossicle of the talus: A case report. Issue 25 (June 2018) - Hong, Chang Hwa; Lee, Young Koo; Won, Sung Hun; Lee, Dhong Won; Moon, Sang Il; Kim, Woo Jong
Abstract: Rationale: Tarsal tunnel syndrome (TTS) is a compressive neuropathy of the posterior tibial nerve or one of its branches within the tarsal tunnel that is often caused by a variety of space-occupying lesions, such as ganglia, lipomas, varicosities, neural tumors, trauma, or systemic disease. The os sustentaculi is a small accessory bone, bridged to the posterior aspect of the sustentaculum tali by fibrocartilage. To the best of our knowledge, this is a rare case of successful treatment of TTS caused by the os sustantaculi. Patient concerns: A 37-year-old male presented with insidious onset of right ankle and foot pain for 1 year. He also complained of a tingling sensation and paresthesia from the plantar and medial aspect of the forefoot to the middle foot area along the main distribution of the medial plantar nerve. The symptoms were mild at rest, but increased upon prolonged walking. He had an ankle sprain history during a football game 2 years previously and recurrent ankle sprains had occurred more frequently in this ankle since that trauma. Diagnoses: Plain standing anteroposterior and lateral view radiographic findings of the right ankle reveled an accessory ossicle located posterosuperomedial to the sustentaculum tali. A computed tomography scan showed that the ossicle articulated between the talus and calcaneus. A magnetic resonance image revealed mild bone marrow edema in the ossicle and medial displacement of the tarsal structures. Interventions: Surgery was performed under general anesthesia. The ossicle was delineated from its surrounding structures and was removed. Tension on the nerve was released. Outcomes: The patient's pain and hypoesthesia were immediately relieved, and the tingling sensation disappeared 6 months after surgery. The patient had no complications or recurrence of symptoms at the 1-year follow-up.